“ESTRATEGIAS METODOLÓGICAS ACTIVAS PARA LA MOTIVACIÓN DE LA LECTURA EN EL TERCER AÑO DE EDUCACIÓN GENERAL BÁSICA EN LA UNIDAD EDUCATIVA “VIGOTSKY” CANTÓN RIOBAMBA AÑO LECTIVO 2018-2019” - Maldonado Bonilla, Jimsop Marco (2020)
This research is intended to evidence that the challenges to improve learning are getting bigger and it is essential that the teacher is trained in the management of methodological tools. This project helped to know the strategies used in the Third Year of the Vigotsky Educational Unit, where a survey showed that most use methodological strategies, but they are not enough. The active methodological strategies for the motivation of the reading were described, the majority of students are not interested in the reading for that reason the theme of this project is active methodological strategies for the motivation of the reading, having as objet of study 28 children of the aforementioned institution. The technique used was the observation, it was supported by a practical instrument that is the observation sheet, for data collection, evidencing methodological strategies for the motivation of reading has a close relationship with the specific objectives, son in theoretical framework the importance of the motivation of reading, benefits such as memory, language, imagination and the capacity for abstraction; Applying a survey, it was concluded that the active methodological strategies used by the teacher are mostly adequate to encourage reading, but could be implemented more to motivate students. It was established that the use of images in children’s reading can help the infant to reach different abilities such as summarizing, reasoning among others. It is recommended to use active methodological strategies that allow the student to be the main author of the class and can obtain meaningful learning.